The Herschel-PACS North Ecliptic Pole Survey. (10th October 2018) - Pearson, Chris; Barrufet, Laia; Campos Varillas, Maria del Carmen; Serjeant, Stephen; Clements, David L; Goto, Tomotsugu; Im, Myungshin; Jeong, Woong-Seob; Kim, Seong Jin; Matsuhara, Hideo; Sedgwick, Chris; Valtchanov, Ivan
Abstract: A detailed analysis of Herschel/Photoconductor Array Camera and Spectrometer (PACS) observations at the North Ecliptic Pole is presented. High-quality maps, covering an area of 0.44 deg 2, are produced and then used to derive potential candidate source lists. A rigorous quality-control pipeline has been used to create final legacy catalogues in the PACS Green 100 μm and Red 160 μm bands, containing 1384 and 630 sources respectively. These catalogues reach to more than twice the depth of the current archival Herschel/PACS Point Source Catalogue, detecting 400 and 270 more sources in the short- and long-wavelength bands, respectively. Galaxy source counts are constructed that extend down to flux densities of 6 mJy and 19 mJy (50% completeness) in the Green 100 μm and Red 160 μm bands, respectively. These source counts are consistent with previously published PACS number counts in other fields across the sky. The source counts are then compared with a galaxy evolution model which identifies a population of luminous infrared galaxies as responsible for the bulk of the galaxy evolution over the flux range (5–100 mJy) spanned by the observed counts, contributing approximate fractions of 50% and 60% to the cosmic infrared background at 100 μm and 160 μm, respectively.